Supplier development and buyer-supplier relationship strategies-a literature review - Sillanpää, Ilkka; Shahzad, Khuram; Sillanpää, Elina (Inderscience Publishers, 2014)
Academic and corporate interest in supplier development and buyer-supplier relationship has increased substantially in recent years. This paper provides a framework for analyzing the current understanding of supplier development strategies, its impact on performance, and buyer-supplier relationship approaches. There is an increased need for buyers and suppliers to strategically collaborate to build a stronger and long-term relationship. The goal is to get extended understanding in buyer-supplier relationship and supplier development strategies. Supplier development is a process of understanding including four steps 1) supplier assessment, 2) competitive pressure, 3) supplier incentives, and 4) direct involvement. Future research can be more empirical focused including multiple case study in global environment to validate the supplier development strategy approaches and help the organization to develop their supplier’s strategies. The presented literature review offers supplier development strategies for empirical case studies and a systematic way to build buyer-supplier relationships to improve the performance.
Keywords: supplier management; supplier policies and procedures; buyer-supplier relationship; supply chain management; supplier development; fi=Johtaminen ja organisaatiot|en=Management and Organization|